“None Come Closer to Us than These:” Augustine and the Platonists - John Peter Kenney (Religions, 2016)
This paper reflects on the importance of pagan Platonism to one of its most sympathetic Christian interpreters, Augustine of Hippo. Its goal is to uncover what Platonism meant to Augustine and why it mattered so much to him throughout his long career. To that end the essay begins by considering salient developments in the study of Platonism over the last fifty years, with particular attention to several crucial shifts in interpretation and consequent changes in its contemporary representation. It then follows those leads into the study of Augustine, considering closely how he himself described the import of Platonism and what it contributed to his development. Brief consideration is first given to Augustine’s earliest works. Attention then turns to his definitive treatment of the conversionary power of Platonism in Book VII of the Confessions and his later assessment of Platonism in City of God VIII. That inquiry will offer a basis to conclude with some final observations on the interpretation of Platonism in the study of Augustine.